Can everyone achieve proficiency with the laparoscopic technique? Learning curve patterns in technical skills acquisition - Grantcharov, Teodor P.; Funch-Jensen, Peter (The American journal of surgery, 2009)
The study was carried out to determine the learning curve patterns for basic laparoscopic technical skills. Thirty-seven surgical residents with limited laparoscopic experience performed 10 repetitions of 6 tasks on a virtual-reality trainer (MIST-VR) with standardized distribution of practice. Assessment was based on time, errors, and economy of motion as measured by MIST-VR. Proficiency levels were established by testing experienced laparoscopic surgeons. Four learning curve patterns were determined. Surgeons in group 1 (5.4%) demonstrated proficiency from the beginning; group 2 (70.3%) achieved predefined expert criteria between 2 and 9 repetitions; group 3 (16.2%) demonstrated improvement but was unable to achieve proficiency within 10 repetitions. Group 4 (8.1%) underperformed and showed no tendency of skills improvement, reflecting a group of subjects who probably are unable to learn laparoscopic technique. The results indicated that a group of subjects could not reach proficiency in the psychomotor skills relevant for laparoscopy. We believe that this is an important issue that should be addressed in future research.